Factors influencing the decision to choose online purchasing on multinational e-commerce platforms: A case study of Vietnamese consumers - Hung, Le Van; Uong, Lan Ngoc Thi (Edelweiss Applied Science and Technology, 2025)
In the context of globalization and the rapid development of digital platforms, this study aims to understand the factors influencing Vietnamese consumers’ decisions to choose online purchasing on multinational e-commerce platforms. Quantitative research was conducted through a survey of 355 consumers. The data are analyzed in steps that include reliability testing of scales using Cronbach’s Alpha, as well as convergent and discriminant validity testing via exploratory factor analysis, followed by correlation and linear regression analyses. The results indicate that eight factors positively affect the decision to choose online purchasing on multinational e-commerce platforms among Vietnamese consumers, including facilitating conditions, habits, performance expectancy, perceived value, social influence, effort expectancy, beneficial motivation, and trust. The study provides insight into the current state of online consumption of Vietnamese consumers. Based on the analysis results, several implications are suggested to promote online purchasing on multinational e-commerce platforms in Vietnam.